Transplanting cells from old but not young donors causes physical dysfunction in older recipients. Issue 3 (23rd January 2020) - Wang, Binsheng; Liu, Zukai; Chen, Vicky P.; Wang, Lichao; Inman, Christina L.; Zhou, Yueying; Guo, Chun; Tchkonia, Tamar; Rowe, David W.; Kuchel, George A.; Robson, Paul; Kirkland, James L.; et al.
Abstract: Adipose‐derived mesenchymal stem cell (ADSC)‐based regenerative therapies have shown potential for use in many chronic diseases. Aging diminishes stem cell regenerative potential, yet it is unknown whether stem cells from aged donors cause adverse effects in recipients. ADSCs can be obtained using minimally invasive approaches and possess low immunogenicity. Nevertheless, we found that transplanting ADSCs from old donors, but not those from young donors, induces physical dysfunction in older recipient mice. Using single‐cell transcriptomic analysis, we identified a naturally occurring senescent cell‐like population in ADSCs primarily from old donors that resembles in vitro‐generated senescent cells with regard to a number of key pathways. Our study reveals a previously unrecognized health concern due to ADSCs from old donors and lays the foundation for a new avenue of research to devise interventions to reduce harmful effects of ADSCs from old donors. Abstract :